Analisis Faktor-Faktor Yang Memengaruhi Pengungkapan Corporate Social Responsibility (CSR) Pada Perusahaan PertambanganYang Terdaftar Di BEI Pasca Pandemi Covid-19 - Mentari, Mila; Indriani, Eni; Astuti, Widia (Fakultas Ekonomi dan Bisnis Unram, 2024)
The research is intended to examine the influence of company size, profitability, leverage and liquidity on Corporate Social Responsibility (CSR) disclosure in mining companies listed on the IDX for the 2020-2022 period. The type of research used is quantitative research. The sample was obtained using a purposive sampling method and 26 companies were selected whose data would be analyzed using the multiple linear regression method. Based on the results of data processing, it can be concluded that the variables of company size and liquidity do not have a significant effect on CSR disclosure. Meanwhile, profitability and leverage have a significant effect on CSR disclosure.